2016
DOI: 10.1155/2016/9827956
|View full text |Cite
|
Sign up to set email alerts
|

Histogenesis of the Oesophagus of Guinea Fowl (Numida meleagris) at Prehatch and Posthatch

Abstract: The histogenesis of the primordial oesophagus was studied to determine the period in which the tunics of the oesophagus developed and became functional in the helmeted guinea fowl (Numida meleagris). Eighteen embryos and nine keets were studied at prehatch and posthatch, respectively. Simple columnar epithelium surrounded by mesenchymal cells was obvious at the 8th day of embryonic development. By the 19th day of embryonic development, the four tunics, tunica mucosa, submucosa, tunica muscularis, and tunica ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The present findings revealed that the oesophagus of the quail was divided into three parts; cervical, crop and thoracic parts similar to those reported in quails (Wilkinson et al., 2018; Zaher et al., 2012), common quail (Parchami & Dehkordi, 2011), rock doves (Shawki et al., 2021), Eurasian collared doves (El‐Mansi et al., 2021), homing pigeon (Kadhim & Mohamed, 2015), guinea fowl (Gosomji et al., 2016), geese (Shehan, 2012), Grey‐Backed Shrike (Zhu, 2015), partridge (Rossi et al., 2006) and white stork (Rus et al., 2000). In contrast, the oesophagus of captive bustards (Bailey et al., 1997), rheas (Rodrigues et al., 2012) and white‐breasted kingfisher (Al Kinany, 2017) consists of two parts; cervical and thoracic, with no crop.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present findings revealed that the oesophagus of the quail was divided into three parts; cervical, crop and thoracic parts similar to those reported in quails (Wilkinson et al., 2018; Zaher et al., 2012), common quail (Parchami & Dehkordi, 2011), rock doves (Shawki et al., 2021), Eurasian collared doves (El‐Mansi et al., 2021), homing pigeon (Kadhim & Mohamed, 2015), guinea fowl (Gosomji et al., 2016), geese (Shehan, 2012), Grey‐Backed Shrike (Zhu, 2015), partridge (Rossi et al., 2006) and white stork (Rus et al., 2000). In contrast, the oesophagus of captive bustards (Bailey et al., 1997), rheas (Rodrigues et al., 2012) and white‐breasted kingfisher (Al Kinany, 2017) consists of two parts; cervical and thoracic, with no crop.…”
Section: Discussionsupporting
confidence: 70%
“…It appears during the period from the 4th day of incubation till the end of the 7th day of incubation, which can be visible grossly as a pouch on the right side. However, the crop appears on the 7th day of incubation in Dandarawi chickens (Hashem, 2018), 8th day in guinea fowl (Gosomji et al., 2016) and on the 11th day of incubation in pheasants (Dehghani et al., 2017). This difference could be attributed to the difference in bird species.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Guinea Fowl (Numida meleagris). The tunics of the muscularis are not well developed till at posthatch 54 . The muscular layers of the human esophagus develop in similar sequence to quail.…”
Section: Discussionmentioning
confidence: 99%
“…The avian oesophagus is a thin‐walled muscular tube situated on the right side of the neck and dorsal to the trachea that comprised of cervical and thoracic regions (Gosomji et al., 2016).…”
Section: Introductionmentioning
confidence: 99%